Cognitive constraints, contraction consistency, and the satisficing criterion - Christopher J. Tyson (Queen Mary University of London, Department of Economics, 2007)
A theory of decision making is proposed that offers an axiomatic basis for the notion of satisficing postulated by Herbert Simon. The theory relaxes the standard assumption that the decision maker always fully perceives his preferences among the available alternatives, requiring instead that his ability to perceive any given preference be decreasing with respect to the complexity of the choice problem at hand. When complexity is aligned with set inclusion, this exercise is shown to be equivalent to abandoning the contraction consistency axiom of classical choice theory.
Keywords: D01; D11; D80; 330; Choice function; Perception; Revealed preference; Threshold; Entscheidungstheorie; Offenbarte Pr\~AƒÂferenzen; Kognition; Theorie